Analisis Ketersediaan dan Kebutuhan Serta Strategi Pengembangan Taman Sebagai Ruang Terbuka Hijau Di Kota Jambi - Sriui; Hutwan Syarifuddin; Asni Johari (Universitas Jambi, 2019)
The research objective was to determine the efforts that had been made in fulfilling the availability of parks, analyzing the broad needs of public parks based on the size of the area and the number of residents and developing a strategy for developing parks in Jambi City. This research was conducted through surveys and direct observations in the field (observation). Data collection is needed to analyze the needs of the park area in Jambi City. Data is collected in the form of primary data and secondary data. The data used in this study include administrative data, physical data, social demographic data and other data that support research. Details of the data are in the form of the Jambi City Administration map, the 2013-2033 Jambi City spatial plan map (RTRW), satellite imagery maps, legislation and regulations relating to green open space, area and population. Data collection techniques are interviews, observation and documentation. The results of the study show that the area of ​​the park in Jambi City is not sufficient for the amount of park needed based on the area and population. Several analyzes were carried out through descriptive analysis, a combination of quantitative qualitative and SWOT analysis. To overcome this problem, a number of park development strategies are needed. The strategies for the availability and development needs of the park as a green open space in Jambi City include: increasing the area of ​​public parks in fulfilling the intrinsic and extrensic functions that can be utilized by the community at large and together, raising awareness of the importance of parks, and the use and use of appropriate technology and the need to innovate, increase participation and cooperation with private sector / other business entities in planning and implementation, and socialize the availability of park functions for life and the environment